Unjuk Kerja Mesin Pemanen Padi Combine Harvester Merek Crown Tipe CCH-2000 Star di Kecamatan Sragi, Lampung Selatan - Nugraha, Danang Rezki; Asmara, Sandi; Oktafri, Oktafri; Lanya, Budianto (Jurnal Agricultural Biosystem Engineering, 2022)
Almost all regions in Indonesia do not have a large availability of labor, therefore mechanical devices are needed to replace them, especially in terms of harvesting shortages of labor can be replaced by mechanical devices such as combine harvester rice harvesting machines. Rice harvesting machine Combine Harvester type ridding brand Crown Type CCH-2000 Star is an agricultural machine that functions to harvest rice through the stages of linking, directing, cutting, bringing the results of pieces, shedding, and cleaning the grain which is done in an integrated manner in one process. The purpose of this study was to find out the performance of the Combine Harvester machine for rice harvesting. This research consists of three main stages, namely machine and land preparation, machine performance testing and data analysis. The parameters observed were work speed, theoretical field capacity, effective field capacity, field efficiency, grain harvest losses, and fuel consumption carried out in May in Sragi District, South Lampung using Combine Harvester machines. The results showed that the engine working speed was 3.38 km/h while the tests carried out by the Center for Agricultural Mechanization Development were 3.90 km/hr. Effective field capacity of 0.77 ha/hour, theoretical field capacity of 0.33 ha/hour, and field efficiency of 42.85%. The percentage of harvest shrinkage in an area of 1 hectare is 0.9% better than the loss with conventional harvesting of up to 18.75%. Fuel consumption when harvesting with an area of 1 ha with 2100 rpm consumes fuel at 16.8 liters/ha. Keywords: Combine Harvester, Machine Performance, Previous Research, Rice.